Le Chiese sui iuris in daspora Le tradizioni orientali e le possibili modalità della loro "implantatio" in Occidente - Szabó, Peter (Ius missionale, 2008)
Sui iuris Churches in Diaspora, Oriental Traditions and Possible Ways of Their "Implantatio" in the West - This study tries to point out the effective benefits of the heritage lived out by the immigrant oriental rite groups in their host autochthon Church and thereby for the "Ecclesia universa" too. By returning to the essential sources of the faith through the experience of other traditions, members of the host Church get the opportunity also to return to their own roots. In fact the diverse cutural backgrounds have provided different emphases, through which the different ecclesiastical traditions explain many important elements of the "deposit of the faith" in considerably varied perspectives and profoundness. This is essential for a integral transmission of our knowledge of the "depositum" gained over the course of history. Since the communities of the Near-East are sociologically dissapearing, the survival of (at least parts of) their living tradition in the diaspora is really of public interest for the whole Church. Considering the hopeless future prospects of their homelands, one of the necessary steps for their survival - if not in fact the only chance of some of them - seems to be the formation of "ritual enclaves" in the framework of the Latin dioceses of the West, not excluding the possibility of some members of the host diocese joining them too. This study refers also to some practical questions in this respect. It is asked, in the end, whether one important long-term result of an "enclave system" could be the re-establishment of the ancient rule of the undivided episcopal jurisdiction (Nic. Can. 8)